Risk assessment of rail transit systems with variable renewable energy based on uncertain random theory - Yanbo Chen; Xiaoxue Li; Zhi Zhang (International Journal of Electrical Power & Energy Systems)
Variable renewable energy access to rail transportation is an effective way for electrified railroads to realize their own efficient and renewable energy use, however, the uncertainty of variable renewable energy also brings risks to the reliable transportation of railroad. Evaluating the operational risk of rail transit systems with variable renewable energy is particularly crucial, but the absence of operation data for variable renewable energy equipment in rail transportation complicates risk assessment. Therefore, this research provides a risk assessment method based on uncertain random theory. Firstly, the uncertainty random theory is applied to take the first failure time of the new energy generation equipment and the traditional equipment as an uncertain variable and a random variable, respectively, the value-at-risk function is defined in combination with the consequences of the system failure; next, the competing failure model for the random system is established by thoroughly considering degradation and shock failures; for the uncertain system, the evidence theory’s framework is used to establish the multiple sources imprecise information conflict and fusion model; finally, the consequences of failure of the system are quantified and the value-at-risk calculation method for the rail transit systems with variable renewable energy is propose. The analysis of case studies shows that the suggested method effectively assesses the operation risk of the rail transit systems with variable renewable energy and resolves the risk assessment issue brought about by the absence of operating data for certain equipment in these systems.